High sodium intake does not worsen low potassium‐induced kidney damage. Issue 8 (20th April 2023) - Zhang, Yahua; Arroyo, Juan Pablo; Bock, Fabian; Zhang, Ming‐Zhi; Harris, Raymond C.; Terker, Andrew S.
Abstract: High sodium and low potassium intake have both been linked to poor cardiovascular health outcomes and increased mortality rates. A combination of the two is thought to be particularly detrimental. While mechanisms are multiple, the kidney is an important target of harmful effects and low potassium influences on both proximal and distal nephron segments are especially potent. We recently reported that a combined high sodium/low potassium diet causes kidney injury and that low potassium in isolation can have similar effects. However, how sodium intake alters this process is not well‐understood. Here we tested the hypothesis that a high sodium intake amplifies effects of low dietary potassium on kidney injury. We observed adding high sodium to low potassium caused an expected increase in blood pressure, but did not worsen markers of kidney injury, inflammation, and fibrosis. It also did not increase abundance or phosphorylation of the sodium chloride cotransporter or its regulatory kinases, SPAK and OxSR1, known renal targets of low potassium. Findings support the claim that dietary potassium deficiency, and not high sodium, is a dominant factor affecting kidney injury in animal models of high sodium/low potassium intake. This suggests further investigation is required to identify optimal ranges of sodium and potassium intake in both healthy populations and in those with kidney disease. Abstract : Adding high sodium to a low‐potassium diet caused an expected increase in blood pressure, but did not worsen markers of kidney injury, inflammation, and fibrosis. It also did not increase the abundance or phosphorylation of the sodium chloride cotransporter or its regulatory kinases, SPAK and OxSR1, known renal targets of low potassium. Findings support the claim that dietary potassium deficiency, and not high sodium, is a dominant factor affecting kidney injury in animal models of high sodium/low potassium intake.